The Art of Staying Neutral The Netherlands in the First World War, 1914-1918 - Abbenhuis, Maartje (Amsterdam University Press, 2006)
The Art of Staying Neutral offers a fascinating insight into the problems and challenges associated with neutrality in an age of 'total war'. It explains how the Netherlands upheld and protected its non-belligerency during the First World War despite constant interference from its warring neighbours. Staying neutral was an artform that the Dutch managed to master through clever diplomacy, conscientious adherence to international laws, comprehensive mobilisation of its armed forces, regular patrols of its territorial boundaries, careful policing of its citizens, and a decisive measure of good fortune. The Art of Staying Neutral makes important contributions to the study of neutrality and the domestic history of the Netherlands in this seminal world event.